Visual Sexual Stimuli—Cue or Reward? A Perspective for Interpreting Brain Imaging Findings on Human Sexual Behaviors - Gola, Mateusz; Wordecha, Małgorzata; Marchewka, Artur; Sescousse, Guillaume (Frontiers in Human Neuroscience, 2016)
There is an increasing number of neuroimaging studies using visual sexual stimuli (VSS) for human sexuality studies, including emerging field of research on compulsive sexual behaviors. A central question in this field is whether behaviors such as extensive pornography consumption share common brain mechanisms with widely studied substance and behavioral addictions. Depending on how VSS are conceptualized, different predictions can be formulated within the frameworks of Reinforcement Learning or Incentive Salience Theory, where a crucial distinction is made between conditioned (cue) and unconditioned (reward) stimuli (related to reward anticipation vs reward consumption, respectively). Surveying 40 recent human neuroimaging studies we show existing ambiguity about the conceptualization of VSS. Therefore, we feel that it is important to address the question of whether VSS should be considered as cues (conditioned stimuli) or rewards (unconditioned stimuli). Here we present our own perspective, which is that in most laboratory settings VSS play a role of reward (unconditioned stimuli), as evidenced by: 1.) experience of pleasure while watching VSS, possibly accompanied by genital reaction 2.) reward-related brain activity correlated with these pleasurable feelings in response to VSS, 3.) a willingness to exert effort to view VSS similarly as for other rewarding stimuli such as money, and/or 4.) conditioning for cues (CS) predictive for. We hope that this perspective paper will initiate a scientific discussion on this important and overlooked topic and increase attention for appropriate interpretations of results of human neuroimaging studies using VSS.